Tinjauan Perbandingan Rencana Anggaran Biaya Atap Menggunakan Rangka Kayu Dan Rangka Baja Ringan - Putra, Alfandias Seysna; Maryadi, Ii; P. R., Yudhistira; Rizal, Ibnu; A. R., Rama (Universitas Pelita Bangsa, 2024)
Roof frames generally use wood as a supporting material. However, the difficulty of obtaining wood material makes the price of wood also increase so that it makes the price of wood more expensive and considered no longer efficient to use, so manufacturers began to think of other alternatives as a substitute for wood that can be used as a strong but cheap roof structure. Mild steel is formed which is considered effective for replacing wood as a roof frame material. The purpose of this paper is to find out how much the cost of making a light steel frame with a wooden frame on a type 156 house that uses SNI analysis with research analysis in the field. The results of the research obtained in this study showed that the roof construction work on the span of a type 156 house using a mild steel frame was obtained for Rp. 18,310,000.00. and Roof Frame Construction using a wooden frame of Rp. 25,950,000.00.